DAMPAK PERSAINGAN PERBANKAN TERHADAP PROFTABILITAS DENGAN MODERASI PENETRASI PERBANKAN ASING (STUDI PADA PERBANKAN DI INDONESIA) - Shofi, Fadhoilus; Marsya Aulia Rizkita; Farhani Kautsar Nugraha (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
This research will examine the impact of banking competition and its effect on profitability driven by the entry of foreign banks penetrating the existing banking industry in Indonesia. The type of this research is quantitative research. The sample in this study consists of all commercial banks in Indonesia that are registered with the Financial Services Authority and active up to the time this research was conducted. The sample of this research involves 98 Banks. The analytical tool used in this study is panel data regression analysis to address the influence and moderation of banking penetration. Competition, as assessed by the Lerner index, has a positive and significant impact on bank profitability. The penetration of foreign banks can moderate the relationship between competition and profitability.